Characterization of exosomes derived from IPEC-J2 treated with probiotic Bacillus amyloliquefaciens SC06 and its regulation of macrophage functions - Xu, Xiaogang; Liu, Rongrong; Zhou, Xuqiang; Zhang, Zhongshan; Zhu, Tianjun; Huang, Yingying; Chai, Lan; Wang, Yazhen; Zhao, Zhenlei; Li, Weifen; Mao, Genxiang (Frontiers in Immunology, 2022)
Probiotics can modulate the immune cells of and responses in the gastrointestinal tract to maintain or improve health. However, the mechanisms by which probiotics promote macrophage (Mφ) activity are poorly understood. Here, we evaluated exosomes derived from intestinal epithelial cells treated with Bacillus amyloliquefaciens SC06 (Ba) and investigated the regulation of Mφ phagocytosis, apoptosis, and polarization. We isolated two exosomes from intestinal porcine epithelial cell lines (IPEC-J2) with or without Ba-treatment, named Ba-Exo and Exo, respectively. They had typical sizes and a cup-shaped morphology, and their surfaces presented typical exosomes-associated proteins, including CD63, ALIX, and TSG101. Ba-Exo and Exo could entrer Mφ (3D4/21 cells) effectively. Moreover, an in vitro phagocytosis assay in vitro demonstrated that Ba-Exo can promote phagocytosis of Mφ. Similar to Exo, Ba-Exo had no effect on Mφ apoptosis. Furthermore, Ba-Exo significantly increased inducible nitric oxide synthase expression, declined the expression of Arg-1 in Mφ, and stimulated Mφ polarization to M1. To explore the differences in the regulation of Mφ polarization between Ba-Exo and Exo, we performed reverse transcription quantitative polymerase chain reaction analysis of the small RNAs and found that miR-222 increased in the Ba-Exo group compared to that in the Exo group. These results provide a new perspective on the relationship between probiotics and intestinal immunity.